Identification of a putative tyrosine-O-sulphate (TyrS) receptor possibly functioning in the biosynthetic transport of tyrosine-sulphated proteins in Madin-Darby canine kidney cells. - Liu, J (1993)
By employing an affinity-gel fractionation technique coupled to Western-blot analysis, we have identified a 175 kDa tyrosine-O-sulphate (TyrS)-binding protein present in Madin-Darby canine kidney (MDCK) cells. The binding of this TyrS-binding protein to TyrS covalently bonded to Sepharose gel was found to be pH-dependent, being strong from pH 8.0 down to pH 6.5 and increasingly weak at pH 6.0 and below. Results obtained from Triton X-114 temperature-induced phase separation and sodium carbonate buffer (pH 11) extraction experiments indicated that the TyrS-binding protein is an integral membrane protein. This 175 kDa TyrS-binding protein was found to be present in association with a major tyrosine-sulphated protein, the apically secreted 80 kDa glycoprotein (gp 80), in cell lysate prepared from MDCK cells maintained under normal growth conditions. When the cell lysate used was prepared from MDCK cells pretreated with 20 mM sodium chlorate, a metabolic sulphation inhibitor, the complex formed between the two proteins could no longer be detected, indicating that the binding of the TyrS-binding protein is through the TyrS residue(s) of gp 80. Both cell-surface biotinylation and cell-surface trypsinization studies demonstrated the predominantly, if not exclusively, intracellular location of the TyrS-binding protein. Furthermore, radioactive pulse-chase experiments revealed that the newly synthesized radiolabelled fibronectin and gp 80 were present in complexes with the TyrS-binding protein in MDCK cells pulse-labelled with [35S]methionine or [35S]sulphate. Exogenous [35S]methionine-labelled gp 80 added to the medium, on the other hand, was not found to be present in association with the TyrS-binding protein in MDCK cells over a 2-h time course. These results strongly suggested the identity of the 175 kDa TyrS-binding protein as a putative 'TyrS receptor', possibly functioning in the biosynthetic transport of tyrosine-sulphated proteins in MDCK cells.